The Role of Parenting in the Development of Talents and Interest of Children - Dea Agustianti; Jazariyah Jazariyah (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
In the process of nurturing and educating children, not all parents appreciate the talents possessed by their children. Parents only educate children in general terms, such as educating children to have good behavior, educating children to study hard without paying attention to children's interests and talents so that children's talents cannot develop optimally due to lack of support from parents. The purpose of this research is to determine the role of parents in developing early childhood talents with parenting styles that are applied by parents at home. The research method used is descriptive qualitative by taking data from a questionnaire distributed to respondents, namely parents and guardians of children who live in Cirebon and Majalengka. The results of this study are that 91.3% of parents and guardians of children have implemented democratic parenting in their care and as many as 8.7% of parents and guardians of students still apply permissive parenting. In this case, parents also play an important role in developing children's talents, namely as motivators and facilitators.